CAMBRIAN REEF FORMATION IN RUSSIAN TERRITORY - Kuznetsov V.G. (My University, 1998)
The Cambrian reef formation was limited by the Early and Middle Cambrian epochs and culminated in the Lenian-early Amgian time. Reef builders of that time were not diverse, and their agglutinative forms prevailed over ahermatypic and, certainly, hermatypic reef-builders. Accordingly, the buildups had a flattened shape and gentle slopes. Relations between reefs and geotectonic structures of the oceanic and continental types are outlined.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская